2008
DOI: 10.1590/s0037-86822008000200016
|View full text |Cite
|
Sign up to set email alerts
|

Investigação sorológica de casos subclínicos de leishmaniose tegumentar após um surto em uma localidade endêmica

Abstract: RESUMOInvestigou-se casos subclínicos de leishmaniose tegumentar em um bairro de Maringá-Paraná, pelas reações de imunofluorescência indireta e enzimaimunoensaio. Das 130 amostras analisadas, uma amostra apresentou título 40 e três apresentaram título 20 pela imunofluorescência indireta, enquanto 11 amostras apresentaram-se positivas pela reação de enzimaimunoensaio. Estes dados sugerem a existência de casos subclínicos nesta localidade.Palavras-chaves: Leishmaniose tegumentar. Imunofluorescência indireta. Enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…A previous study identified 11 (8.5%) ELISApositive samples from among 130 healthy individuals living in an endemic region in Maringá city, Paraná (Arraes et al, 2008), which is in agreement with the results presented in this study (19.5%). Some studies identified higher percentages of subclinical cases in the metropolitan area of Recife and the Federal District (67% and 71.8%), respectively (Brito et al, 2008;Sampaio et al, 2009), which the authors attributed to peri-domicile transmission.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…A previous study identified 11 (8.5%) ELISApositive samples from among 130 healthy individuals living in an endemic region in Maringá city, Paraná (Arraes et al, 2008), which is in agreement with the results presented in this study (19.5%). Some studies identified higher percentages of subclinical cases in the metropolitan area of Recife and the Federal District (67% and 71.8%), respectively (Brito et al, 2008;Sampaio et al, 2009), which the authors attributed to peri-domicile transmission.…”
Section: Resultssupporting
confidence: 93%
“…The high ACL endemicity may explain the presence of subclinical forms of the disease in these municipalities. Previous studies have also reported the presence of subclinical cases in municipalities with high ACL endemicity (Arraes et al, 2008;Sampaio et al, 2009).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations